Anterior Segment Optical Coherence Tomography Angiography Following Trabecular Bypass Minimally Invasive Glaucoma Surgery - Gan, Jinyuan; Sng, Chelvin C. A.; Ke, Mengyuan; Chieh, Chew Shi; Tan, Bingyao; Schmetterer, Leopold; Ang, Marcus (Frontiers in Medicine, 2022)
Objective: To assess anterior segment optical coherence tomography angiography (AS-OCTA) imaging of the episcleral vessels before and after trabecular bypass minimally invasive glaucoma surgery (MIGS). Design: A prospective, clinical, single-center, single-arm study conducted at Singapore National University Hospital Subjects: Patients with glaucoma or ocular hypertension undergoing Hydrus Microstent (Ivantis Inc. Irvine, CA, USA) implantation, who require at least one intra-ocular pressure lowering medication. One or two eyes per patient may be enrolled. Methods: Institutional Review Board approved. We performed AS-OCTA (Nidek RS-3000 Advance 2, Gamagori, Japan) pre- and up to 6 months post-MIGS implantation using a standard protocol in all cornealimbal quadrants, to derive episcleral vessel densities (VD) using a previously described technique. Main Outcome Measures: Episcleral VD pre- and post-surgery, in sectors with and without the implant. Results: We obtained serial AS-OCTA images in 25 eyes undergoing MIGS implantation (23 subjects, mean age 70.3 ± 1.5, 61% female) with mean preoperative intraocular pressure (IOP) of 15.5 mmHg ± 4.0. We observed reductions in postoperative episcleral VD compared to preoperative VD at month 1 (mean difference -3.2, p=0.001), month 3 (mean difference -2.94, p=0.004) and month 6 (mean difference -2.19, p=0.039) in sectors with implants (overall 6 month follow-up, p=0.011). No significant changes were detected in episcleral VD in the sectors without implants (p=0.910). Conclusion: In our pilot study, AS-OCTA was able to detect changes in the episcleral VD following trabecular bypass MIGS, which may be a useful modality to evaluate surgical outcomes if validated in future studies.